Child temperament, parent emotions, and perceptions of the child's feeding experience - Hughes Sheryl O; Shewchuk Richard M (BMC, 2012)
Abstract Background Associations between parent and child characteristics and how they influence the approach parents take toward children in the feeding environment have not been examined extensively, especially in low-income minority families who are at a higher risk for obesity. The primary aim of the study was to examine positive and negative parent emotions as potential mediators of the relationship between child temperament and parents' perceptions of strategy effectiveness and problems encountered in feeding children fruit and vegetables. Methods Participants were low-income families (n = 639, 73% minority, children aged 3-5 years) participating in Head Start programs in two states. Parents completed the Children's Behavior Questionnaire (CBQ), Positive and Negative Affect Schedule (PANAS), and measures of strategy effectiveness (teachable moments, practical methods, restriction, and enhanced availability) and problems encountered (vegetable characteristics, child attributions for dislike, external influences, and parental demands) in feeding children fruit and vegetables. Results Positive parent emotions partially mediated the relationship between child Effortful Control and strategy effectiveness and fully mediated the relationship between Surgency and strategy effectiveness. Although negative parent emotions were associated with increased perception of problems in feeding children fruit and vegetables, the relationship between Negative Affectivity and problems in feeding was partially mediated by negative parent emotions. Conclusions Positive parent emotions facilitated perceived effectiveness of feeding strategies, with child Effortful Control and Surgency instrumental to this process. Understanding mechanisms in parent-child feeding is important when developing interventions designed to promote healthy child eating behaviors.